Estratégias para implantação de um banco de leite humano: posição dos profissionais e gestores - Rechia, Flavia Pinhão Nunes de Souza (2017)
Breastfeeding provides a complete meal for the child, protecting against infectious diseases, and it is an important factor in reducing child mortality, as well as a strong allied in child development. For premature infants, it provides nutritional, immunological and psychological benefits, as well as reducing hospital stay. Milk banks integrate public policy strategies for breastfeeding (promotion; protection; support). Offering milk as the first food option for at-risk newborns and/or sick babies it is also aimed. In Rio Grande do Sul there are only ten milk banks. There is a need for expanding milk banks, especially in regions with the highest number of neonatal intensive care unit beds. Objectives: 1) to know the health professionals` stands and managers` stands about maternal and child health area regarding the implantation of a milk bank at a university hospital; 2) to discuss the strategies for its implantation. Method: Quantitative-qualitative study; Participative research; the data collection was divided in two phases: the first was a questionnaire about the perception of the need to implant a milk bank, which was answered by 119 participants from maternal and child health from the University Hospital. The results triggered the discussions during second phase; the Focal Group was composed by representatives of professionals and managers. The group met in three sessions; they met to discuss the facilities and difficulties about the milk bank implementation, strategies and referrals. Transcripts were submitted to content analysis. The ethical aspects about human research were respected following the resolution 466/12 from National Health Council. Results: Most respondents perceive the need to establish a milk bank as necessary. The content analysis from focal group transcripts resulted in three categories referring the discussion about need to implement a milk bank: benefits, potentialities and weaknesses. The benefits include the population and the institution contributing to the assistance, education, research and extension. The potentialities are: hospital coverage, institutional organization and staffing. Among the weaknesses: infrastructure resources, managers support, human resources and financial resources. The discussion about potentialities and fragilities generated the referrals to strengthen the milk bank implantation. Conclusion: Implementing a milk bank extends the possibilities for training professionals, enabling them on breastfeeding management. It is necessary for professionals and managers to recognize that the milk bank goes beyond breastfeeding; it encompasses a social commitment capable of promoting the population rights and ensuring compliance to public health policies.